The sociology of bullying : power, status, and aggression among adolescents - Donoghue, Christopher (Critical perspectives on youth., 2022)
"This book takes form in this edited volume on aggressive adolescent behavior that employs sociological theories and empirical research to better understand the social aspects of bullying. Leading sociologists and other social scientists consider ways in which a sociological understanding of bullying can advance research and inform anti-bullying school policies"--